Elements of rhythm in apparatus movements: training gymnasts - Suprun A.A. ,; Medvedeva E.N. ,; Vlasova N.Yu. ,; Borisova V.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to based on the evaluation of the impact of electrical stimulation of the primary muscle groups and the kinematic characteristics of movements during the execution of technical maneuvers with an object to music with varying rhythmic patterns, we aim to determine the focus of subject training in rhythmic gymnastics. Methods and structure of the study. To investigate the mechanics of motion in elite athletes (n=12), we employed the Qualisys optoelectronic system, which includes the Qualisys Track Manager (QTM) software. Results and conclusions. The findings of the research allowed us to pinpoint the areas of focus for subject training in order to develop the rhythmic abilities of athletes at various stages of long-term training in rhythmic gymnastics. The focus of subject training for mastering the tempo-rhythmic structure of movements of an object, based on the identified factors that influence them, will be: enhancing coordination abilities, improving inter-muscular coordination, increasing the level of subject, musical, motor, and compositional preparedness of athletes, utilizing the subject as a means to create an image in the composition of gymnasts, and achieving high performance in competitive activities through proficiency in the majority of technical elements of the all-around.